1997
DOI: 10.1021/bi9713052
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure at 1.1 Å Resolution of α-Conotoxin PnIB:  Comparison with α-Conotoxins PnIA and GI

Abstract: Conotoxins are small, cysteine-rich peptides isolated from the venom of Conus spp. of predatory marine snails, which selectively target specific receptors and ion channels critical to the functioning of the neuromuscular system. alpha-Conotoxins PnIA and PnIB are both 16-residue peptides (differing in sequence at only two positions) isolated from the molluscivorous snail Conus pennaceus. In contrast to the muscle-selective alpha-conotoxin GI from Conus geographus, PnIA and PnIB block the neuronal nicotinic ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 31 publications
1
65
0
Order By: Relevance
“…EpI is constructed with 4 residues in loop one and 7 residues in loop two and was anticipated to have a structure similar to those reported for PnIA and PnIB (41,42). Compared with other 4/7 framework ␣-conotoxins, EpI has homology to both loop one and loop two of PnIA and PnIB and to loop one of MII (see Table I).…”
Section: Discussionmentioning
confidence: 95%
“…EpI is constructed with 4 residues in loop one and 7 residues in loop two and was anticipated to have a structure similar to those reported for PnIA and PnIB (41,42). Compared with other 4/7 framework ␣-conotoxins, EpI has homology to both loop one and loop two of PnIA and PnIB and to loop one of MII (see Table I).…”
Section: Discussionmentioning
confidence: 95%
“…The folding of conopeptides is mainly determined by their cysteine framework and the spacing between the cysteine residues, while the final folding of the peptide involves non-covalent interactions among non-cysteine residues [33]. However, depending upon the significant variation in spacing between the cysteines, a conserved fold may or may not be formed [42]. From the three dimensional structures known so far, conotoxins can broadly have four structural backbone folds [13].…”
Section: Foldingmentioning
confidence: 99%
“…They have a α4/7 cysteine framework with two disulfide bonds formed between Cys2 -Cys8 and Cys3 -Cys16. Their sequence comparison has shown that they differ at two positions, with Leu10 and Ser11 in PnIB replacing Ala10 and Asn11 of PnIA [42]. The overall structure of the two α-conotoxins are very similar to each other, showing a well superimposed backbone and similar side chains in most cases [42].…”
Section: Three-dimensional Structure Of Native Conotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In structures of the 4/7 ␣-conotoxins determined by x-ray crystallography, PnIA, PnIB, and EpI, a region of 3 10 helix is observed N-terminal to the ␣-helix (7,8,10). There are no solution structures reported for these molecules, but ImI has the same first loop as EpI, and four independent solution structures of ImI have been reported.…”
Section: Fig 7 Effect Of Native and Ribbon Isomers Of Auib On Nicotmentioning
confidence: 99%